2020
DOI: 10.1051/matecconf/202030500040
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the flooding speed of former lignite open pits on the stability of final slopes

Abstract: Flooding the residual gaps of former lignite open pits is often applied worldwide, offering opportunities for the use of the lake and the reclaimed land, as well as many benefits, ranging from the restoration of ecosystems to the development of the local economy. The flooding process is conditioned by the available quantities of water from natural and/or artificial sources. Flooding can be done either by natural methods (underground water inflow plus intake of water from rainfall and superficial drainage), or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 2 publications
1
5
0
Order By: Relevance
“…As can be seen, the safety factor was higher when a slope was completely submerged than in the case of the same slope, but partially submerged; this was a result of the manifestation of hydrostatic pressure on the surface of the slope, which acts as a support prism. Analyzing carefully, it can be observed that every time the water level rose on the surface of a slope, the safety factor encountered a significant decrease, followed by a significant increase-the same results were recently observed, according to [49].…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…As can be seen, the safety factor was higher when a slope was completely submerged than in the case of the same slope, but partially submerged; this was a result of the manifestation of hydrostatic pressure on the surface of the slope, which acts as a support prism. Analyzing carefully, it can be observed that every time the water level rose on the surface of a slope, the safety factor encountered a significant decrease, followed by a significant increase-the same results were recently observed, according to [49].…”
Section: Discussionsupporting
confidence: 77%
“…The evolution of the safety factor of the final slopes depends directly on the duration of the flooding process [49]. The flood duration depends on the volume of the remaining gap and the available water flow from natural or artificial sources, being defined by the ratio between the two elements: the volume, V, and, respectively, the flow, Q.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Decommissioning the dewatering systems, restoring the aquifer resources, and raising the water level in the lake, influences the stability of the slopes negatively, by manifesting the pore water pressure and/or the hydrodynamic pressure under the conditions of formation of aquifers currents, but also positively by the water pressure manifested on the surface of the slope. Knowing the behavior of rocks in contact with water and the geotechnical risks that may occur in the newly created conditions is essential for increasing the security and safety of objectives and people in areas of influence [31,32].…”
Section: Criterion C6-stability Conditions Of the Final Slopesmentioning
confidence: 99%
“…Among them, the most important are represented by the speed and duration of the flooding process, the stability of the in situ and dump slopes, and the geochemistry of the rocks. Some researchers have studied the influence of various factors on the flooding process of the remaining gaps [3], [5], [6], but, generally, particular focus was given to factors in-fluencing slope stability [7]- [10]. Therefore, in this paper, we aimed at identifying the most important factors influencing the flooding process taking into account both the factors influencing the speed and duration of this process and those influencing the stability of the slopes, as they cannot be neglected and safety must prevail.…”
Section: Introductionmentioning
confidence: 99%